MENUMBUHKAN KARAKTER RASA INGIN TAHU SISWA DALAM PEMBELAJARAN SEJARAH MELALUI MEDIA PUZZLE - Millati Silmi; Yani Kusmarni (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
The title of this research is “Growing up Students’ Curiosity Character in Learning History Through Puzzle Media in Class XI MIA 3 SMA Negeri 1 Lembang”. This research was held in Class XI MIA 3 SMA Negeri 1 Lembang. This research was motivated by the low of students’ curiosity character in learning history. The purpose of this research is how to grow the students’ curiosity in learning history among senior high school student, because most of them have wrong perception about learning history that considered as a boring lesson and only focused on text memorize without get the comprehensive perception related to the historical events. The developed indicators of the curiosity character in this research are the ability to ask questions, ability to answer questions from friends or teachers, ability to find out the information from books and the internet, then to contribute in group activities and class discussions, ability to interpret images in puzzles, and the ability to provide solutions of each questions in student work sheet (LKS). The research method used in this research is a Classroom Action Research (PTK) by Kemmis and Mc Taggart. It consists of several stages, including the planning, implementation, observation and reflection. Based on the results of research, the character of the students’ curiosity in learning history has increased. It could be seen from the percentage that indicates students’ significant change. The percentage showed the change of students’ curiosity character which was not good enough to the good category. It can be a good recommendation for teachers or school to develop the learning process to grow students’ curiosity character, so that the learning would be more meaningful.